Implications of the NHS workforce plan - Max Warner; Ben Zaranko (Institute for Fiscal Studies (IFS), 2023)
The NHS workforce plan aims for a large expansion in health service staffing. We examine the potential implications for NHS funding.
Keywords: 330; Government finances and spending; Health and social care; IFS Green Budget 2023; NHS; Employment; Government spending; Health; Healthcare; Labour supply and workforce; Public finance; Public sector